Heparin Binding Protein for the Early Diagnosis and Prognosis of Sepsis in the Emergency Department: The Prompt Multicenter Study. Issue 4 (14th April 2022) - Katsaros, Konstantinos; Renieris, Georgios; Safarika, Asimina; Adami, Evangelia-Maria; Gkavogianni, Theologia; Giannikopoulos, George; Solomonidi, Nicky; Halvatzis, Stamatios; Koutelidakis, Ioannis M.; Tsokos, Nikolaos; Tritzali, Maroula; Koutoukas, Pantelis; et al.
ABSTRACT: Background: The validation of new biomarkers for the diagnosis and risk stratification of patients with sepsis at an early point is essential for successful treatment. Recent publications prompted us to investigate of heparin binding protein (HBP) for the emergency department (ED) admissions. Materials and Methods: In this multicenter, cross-sectional study, HBP and procalcitonin (PCT) were measured within the first hour upon admission to the ED in plasma samples of 371 patients with signs of infection. Patients were classified into non-sepsis and sepsis by the Sepsis-3 definitions and were followed up for outcome. Results: HBP was significantly higher in patients with sepsis and was positively correlated to PCT and C-reactive protein, absolute neutrophil and monocyte counts, creatinine, bilirubin and lactate. Sensitivity, specificity, positive predictive value, and negative predictive value of HBP more than 19.8 ng/mL for the diagnosis of sepsis was 66.3%, 44.9%, 49.3%, and 62.2%, respectively; and for prediction of early death was 100%, 41.0%, 4.5%, and 100%, respectively. Single HBP and PCT could not predict 28-day mortality; this was performed with sensitivity, specificity, positive predictive value, and negative predictive value 44.8%, 81.8%, 17.3%, and 94.6% when used in combination. Conclusion: Admission HBP can be used as a tool for the early diagnosis of sepsis and for the risk of early death in the ED.